Pengaruh Fitur BSI Mobile Dan Kemudahan Bertransaksi Terhadap Kepuasan Nasabah Di BSI Kc Madiun Agus Salim - Khotijah, Dewi; Yunita, Ratna (WADIAH, 2024)
This research was conducted to analyze how the influence of mobile BSI features and the ease of transactions on customer satisfaction at BSI KC Madiun Agus Salim. The data in this study were collected by distributing questionnaires and the data was processed using SPSS 21 software with multiple linear regression analysis tests. The samples taken were 100 respondents with probability sampling technique. The results of the analysis show that the mobile BSI feature (X1) and ease of transaction (X2) have a positive and significant effect on customer satisfaction partially or simultaneously. Other results show that the variable that greatly influences customer satisfaction at BSI KC Madiun Agus Salim is the BSI mobile feature variable, meaning that the better the BSI mobile feature service is presented, the level of customer satisfaction is also increasing. Thus, companies must always strive to improve and bring innovative features to BSI mobile. Keywords: BSI Mobile Features, Ease of Transactions, and Customer Satisfaction